2021
DOI: 10.1177/10534512211001837
|View full text |Cite
|
Sign up to set email alerts
|

African American Parents With Children With Disabilities: Gathering Home–School Reflections

Abstract: African American families are multidimensional entities that change over time. This is particularly true when there is a child with a disability in the family. The communication and interaction of the family and parents with the teachers and school in which their child receives special education services are of crucial importance. The goal for all is a relationship based on equity and parity, but research indicates that often this is not the case for African American parents who have a child with a disability.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 24 publications
(28 reference statements)
0
6
0
Order By: Relevance
“…It is worth underscoring that parents play an integral role in ensuring the scholastic success of their children, including those with SEND (Hornby, 2011 ). Unfortunately, modern reality involves parents having long work days, multiple jobs or additional responsibilities outside of the home that limit the time they can spend supporting their children's education (Brandon et al., 2021 ). For parents of children with special educational needs and disabilities, school closures were an additional stressor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth underscoring that parents play an integral role in ensuring the scholastic success of their children, including those with SEND (Hornby, 2011 ). Unfortunately, modern reality involves parents having long work days, multiple jobs or additional responsibilities outside of the home that limit the time they can spend supporting their children's education (Brandon et al., 2021 ). For parents of children with special educational needs and disabilities, school closures were an additional stressor.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies reported that a substantial minority of parents found that the pandemic yielded positive effects, whereas, a majority of parents of children with SEND reported being negatively impacted by the pandemic. To mitigate the struggles expressed by parents of children with SEND, a future goal must be to create better relationships between parents, teachers and schools, so that home‐schooling can be implemented more effectively and with less stress in the future (Brandon et al., 2021 ). Upon the return of students with SEND to school, teachers will need to take into account the after‐effects of the COVID‐19 pandemic and focus on teaching effective coping skills for children who were negatively impacted by it (Lee et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Likewise, parents of students in a culturally relevant class should be considered co-collaborators in creating and teaching curriculum. Traditional methods of family engagement such as school conferences and notes in backpacks about homework assignments are not sufficient if educators wish to subvert deficit models of marginalized groups (Brandon et al, 2021; Paris, 2012).…”
Section: Culturally Relevant Pedagogymentioning
confidence: 99%
“…As families engage in an ongoing dialogue with educators, they build trust and begin to feel comfortable discussing topics they previously might not have (Lopez et al, 2022). Educators can use preexisting questionnaires that fit their population of students (Brandon et al, 2021; Matute-Chavarria, 2021) or they can create their own prompts based on the needs of their students.…”
Section: Step 3: Building Social Ties Between Familiesmentioning
confidence: 99%
“…13 Elder has found that regular action planning makes the IEP process go smoother because there is increased student and family participation. In addition, engaging historically marginalized families in this way can help practitioners understand what the family needs to feel safe engaging with the school (Brandon et al, 2021; Cavendish et al, 2016). Furthermore, action planning meetings represent an opportunity for practitioners to move toward having active dialogue and debrief about their child’s educational program.…”
Section: Practical Steps To Desegregate Special Education Systemsmentioning
confidence: 99%